2013
DOI: 10.1097/brs.0b013e31827b0d4b
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Risk Factors of the Retropharyngeal Carotid Artery on Cervical Magnetic Resonance Imaging

Abstract: Carotid arterial anomalies occurred in 12.3% of cases; severe aberrancy was present in 2.6% of patients. In elderly females with kyphotic alignment, a high index of suspicion must be raised for aberrancy. Preoperative assessment of the vasculature in the anterior neck may avoid catastrophic complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
27
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 13 publications
2
27
1
Order By: Relevance
“…Prior studies have shown a prevalence of retropharyngeal carotid arteries of 2.6%. 10 The higher prevalence of retropharyngeal carotid arteries between our study and other studies may be related to differences in the method of determining retropharyngeal position and differences in patient demographics. Additionally, some prior studies have only commented on the retropharyngeal position of the internal carotid artery, while our study has shown that the common carotid artery and external carotid artery may also have a retropharyngeal position.…”
Section: Discussioncontrasting
confidence: 49%
See 3 more Smart Citations
“…Prior studies have shown a prevalence of retropharyngeal carotid arteries of 2.6%. 10 The higher prevalence of retropharyngeal carotid arteries between our study and other studies may be related to differences in the method of determining retropharyngeal position and differences in patient demographics. Additionally, some prior studies have only commented on the retropharyngeal position of the internal carotid artery, while our study has shown that the common carotid artery and external carotid artery may also have a retropharyngeal position.…”
Section: Discussioncontrasting
confidence: 49%
“…For this reason, however, our results may not necessarily apply to the population as a whole. Koreckij et al 10 found that an aberrant course to the carotid arteries was more common in female patients and was associated with significantly greater spondylosis and kyphosis than in agematched controls. The retropharyngeal carotid artery is a clinically important anatomic variant, and numerous complications associated with this anatomic variant have been reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients with such an abnormality may require an alternate approach, such as one from the opposite anterior side or a posterior approach. [16]…”
Section: Assessmentmentioning
confidence: 99%